Analysis of Differences in Tariff for Health Service Based on Sustability of Diagnosis on Admision and Summary Discharge Form with INA-CBGs Verification - Oktamianiza Oktamianiza; Deni Maisa Putra; Yulfa Yulia; Agni Fahira; Afridon Afridon (International Journal of Engineering, Science and Information Technology, 2021)
The implementation of the National Health Insurance starting in January 2014 made a change in the payment system from the Retrospective Paymant System to the Prospective Payment System with INA-CBG's rates. The difference in INA-CBG's rates and hospital rates is a fundamental problem so that hospitals must make efforts to achieve quality and cost control. the purpose of this research was to determine the Analysis of Differences in Tariff for Health Service Based on sustability of Diagnosis on the admision and discharge summary form (RM1) with INA-CBGs Verification at Hospital Dr. Reksodiwiryo Padang. The results of the study found that the accuracy of disease diagnosis and patient medical treatment was on the RM1 form (21.7%), on the INA-CBGs verification (56.5%). Differences in disease diagnosis and patient medical treatment on RM1 form with INA-CBGs verification (63.0%), and differences in health service fees based on accuracy of patient diagnosis and medical treatment on RM1 form with INA-CBGs verification (63.0%) . There is a significant relationship between the difference in the Tariff of health services with the accuracy of diagnosis on the RM1 form and the INA-CBGs verification which is quite large, due to the discrepancy in writing the diagnosis on RM1 with the INA-CBGs verification.